2010
DOI: 10.1029/2009jg001151
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐penetrating radar observations of enhanced biological activity in a sandbox reactor

Abstract: [1] In this study, we evaluate the use of ground-penetrating radar (GPR) to investigate the effects of bacterial activity in water saturated sand. A 90-day laboratory-scale controlled experiment was conducted in a flow-through polycarbonate sandbox using groundwater from the Kansas River alluvial aquifer as inoculum. After 40 days of collecting baseline data, bacterial growth was stimulated in the sandbox by the addition of a carbon and nutrient solution on a weekly basis. Radar signal travel time and attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Ideally we would have recorded transmission mode measurements of the direct wave across the peat block; however, this measurement would require two antennas and multiple GPR electronics not at our disposal. We therefore used the reflection mode as previously successfully applied by Comas and Slater [2007] and Schillig et al [2010]. The excellent data quality we obtained indicates that the reflection mode approach sufficiently satisfied our objectives.…”
Section: Methodsmentioning
confidence: 93%
“…Ideally we would have recorded transmission mode measurements of the direct wave across the peat block; however, this measurement would require two antennas and multiple GPR electronics not at our disposal. We therefore used the reflection mode as previously successfully applied by Comas and Slater [2007] and Schillig et al [2010]. The excellent data quality we obtained indicates that the reflection mode approach sufficiently satisfied our objectives.…”
Section: Methodsmentioning
confidence: 93%
“…GPR has been used successfully in the field to detect biogenic gas (Comas et al, 2005;Parsekian et al, 2010Parsekian et al, , 2011. Formation of a separate gas-phase in the pore space would decrease the bulk dielectric constant of the medium and hence increase the velocity of propagation of the radar signal, as observed in the laboratory by Schillig et al (2010). During this experiment, biogenic gas formation is likely to occur during time periods of enhanced biostimulation near the GPR boreholes closest to the ORC.…”
Section: Gas Formationmentioning
confidence: 91%
“…Although the exact value of the dielectric constant of the biomass at Borden still remains unclear, Schillig et al (2010) reported a decrease in 1.2 GHz GPR wave velocity observed during enhanced biostimulation and biomass growth in a sandbox laboratory experiment. The sandbox Fig.…”
Section: Biomass Growthmentioning
confidence: 94%
See 2 more Smart Citations